2018
DOI: 10.4197/med.25-1.2
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of ABO-Rhesus Blood Groups in the Western Region of Saudi Arabia

Abstract: The western region of Saudi Arabia is known as a multinational region with different ethnic groups of people. This study aims to evaluate the ABO and rhesus blood groups among study subjects in the Western area of Saudi Arabia and their comparison with other regions of the Kingdom. It is a retrospective study. 35,388 participants were included. ABO blood grouping was done using tube method. Agglutination in any tube or hemolysis was considered as positive. Blood grouping was done by a preliminary finger prick,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 6 publications
2
6
0
Order By: Relevance
“…Although group O is the most among ABO groups in the population of this study, as seen in daily practice and in the literature [ 30 ], it was less represented in COVID-19 positive patients. This finding was reported in a previous study [ 31 ].…”
Section: Discussionmentioning
confidence: 91%
“…Although group O is the most among ABO groups in the population of this study, as seen in daily practice and in the literature [ 30 ], it was less represented in COVID-19 positive patients. This finding was reported in a previous study [ 31 ].…”
Section: Discussionmentioning
confidence: 91%
“…This was almost consistent with the distribution of blood groups among the Saudi Arabia community: blood group O (52%), A (26%), B (18%), and AB (4%). [25] The results also showed that the upper respiratory tract infection and shortness of breath showed statistically significant differences between the ABO blood group ( P = .014 and P = .009 retrospectively). Moreover, all symptoms were observed highly in blood group O followed by A then B except for pharyngeal exudate observed in blood group A.…”
Section: Discussionmentioning
confidence: 80%
“…Interestingly, another study in the Western province in Jeddah, KSA, showed that COVID-19 infection was more frequent in blood group O (50.1%), while blood group AB disclosed the lowest rate (4.1%), among 35,388 Saudi blood donors (Alzahrani et al, 2018). A recent review by Kabrah et al also reported that individuals with blood group A had significantly higher risks, whereas blood type AB showed lower risks, of acquiring COVID-19 infection (Kabrah et al, 2021).…”
Section: Introductionmentioning
confidence: 98%
“…Interestingly, another study in the Western province in Jeddah, KSA, showed that COVID-19 infection was more frequent in blood group O (50.1%), while blood group AB disclosed the lowest rate (4.1%), among 35,388 Saudi blood donors ( Alzahrani et al., 2018 ). A recent review by Kabrah et al.…”
Section: Introductionmentioning
confidence: 99%